Pengaruh Pengguna Influencer Marketing Dan Promosi Diskon Terhadap Keputusan Pembelian Secara Online Di Marketplace Shopee: (Studi Kasus Pada Masyarakat Jalan Garu II B Harjosari I Kecamatan Medan Amplas) - Junior, Joshua; Hidayat, Toni; Safina, Wan Dian; Lubis, Tukimin (Movere Journal, 2024)
This research aims to find out and analyze the influence of influencer marketing and discount promotions on purchasing decisions in the Shopee marketplace in the people of Jalan Garu II B Harjosari 1, Medan Amplas District. This research uses a descriptive quantitative approach with data collection methods of observation, questionnaires and interviews. The population in this study is the people of Jalan Garu II B Harjosari I, Medan Amplas District and the sample as respondents for this study will be taken using side purposive use with the Slovin formula, namely 100 people met during the research. The data obtained in this research was analyzed using multiple linear regression analysis with the SPSS 22 program. The results of this research show that the calculated F value of 372.095 is greater than the F table of 3.09, which means that simultaneously there is an influence on influencer marketing (X1) and discount promotions (X2) on online purchasing decisions on the Shopee marketplace. Partially, it can be seen that only the influencer marketing (X1) and discount promotion (X2) variables influence purchasing decisions, namely the influencer marketing variable (X1) of 7.686 is greater than the t table of 1.660 and the discount promotion (X2) is 2.982 greater. from the t table of 1.660. Based on the results seen from the coefficient of determination of the influencer marketing variable (X1) and discount promotions (X2), the influence is with an R2 value of 0.885 or 88.5%.